The impact of whiplash injury on temporomandibular joint function: a literature review - Ciecierska, Kinga; Napierała, Michał; Łapiński, Maciej; Zinko, Oksana; Wasilkowska, Krystyna; Zimnoch-Włodarczyk, Aleksandra; Łatkowska, Sylwia; Rzeczycka, Aleksandra; Socha, Wiktoria (Quality in Sport, 2026)
Introduction: Whiplash injuries are one of the most prevalent consequences of traffic collisions and are associated with a wide range of conditions referred to as whiplash-associated disorders (WAD). These manifestations are most commonly associated with pain and limited mobility of the cervical spine. A growing number of research indicates that these injuries may also impair the function of the temporomandibular joints (TMJs), thereby contributing to the development of their subsequent disorders. The aim of the study: The objective of the study was to discuss the correlations and dependency between whiplash injury and temporomandibular joint function. Acquiring this knowledge enables specialists to make precise diagnoses and implement appropriate therapeutic procedures, thereby reducing the risk of misdiagnosis or misdiagnosis omissions. Materials and methods: The following literature review provides a comprehensive discussion of the association between whiplash injuries and temporomandibular joint function. In December 2025, an extensive search of prominent electronic databases (PubMed, Google Scholar) was undertaken in order to identify relevant published studies on this subject. Conclusions: Studies indicate that whiplash injury may impair TMJ function and contribute to the development of TMJ disorders. The mechanisms underlying this relationship may be functional or neurophysiological in nature, but remain under investigation. Symptoms may be transient or persist long-term for several years, underscoring the necessity for a holistic diagnosis and an interdisciplinary therapeutic approach in patients after whiplash injury.